Burrowers from the Past: Mitochondrial Signatures of Ordovician Bivalve Infaunalization. (1st April 2017) - Plazzi, Federico; Puccio, Guglielmo; Passamonti, Marco
Abstract : Bivalves and gastropods are the two largest classes of extant molluscs. Despite sharing a huge number of features, they do not share a key ecological one: gastropods are essentially epibenthic, although most bivalves are infaunal. However, this is not the ancestral bivalve condition; Cambrian forms were surface crawlers and only during the Ordovician a fundamental infaunalization process took place, leading to bivalves as we currently know them. This major ecological shift is linked to the exposure to a different redox environoments (hypoxic or anoxic) and with the Lower Devonian oxygenation event. We investigated selective signatures on bivalve and gastropod mitochondrial genomes with respect to a time calibrated mitochondrial phylogeny by means of dN/dS ratios. We were able to detect 1) a major signal of directional selection between the Ordovician and the Lower Devonian for bivalve mitochondrial Complex I, and 2) an overall higher directional selective pressure on bivalve Complex V with respect to gastropods. These and other minor dN/dS patterns and timings are discussed, showing that the Ordovician infaunalization event left heavy traces in bivalve mitochondrial genomes.